Bottom-Up Fabrication of Sulfur-Doped Graphene Films Derived from Sulfur-Annulated Nanographene for Ultrahigh Volumetric Capacitance Micro-Supercapacitors - Wu, Zhong-Shuai; Tan, Yun-Zhi; Zheng, Shuanghao; Wang, Sen; Parvez, Khaled; Qin, Jieqiong; Shi, Xiaoyu; Sun, Chenglin; Bao, Xinhe; Feng, Xinliang; Muellen, Klaus (Journal of the American Chemical Society, 2017)
Heteroatom doping of nanocarbon films can efficiently boost the pseudocapacitance of micro-supercapacitors (MSCs); however, wafer-scale fabrication of sulfur-doped graphene films with a tailored thickness and homogeneous doping for MSCs remains a great challenge. Here we demonstrate the bottom-up fabrication of continuous, uniform, and ultrathin sulfur-doped graphene (SG) films, derived from the peripherical trisulfur-annulated hexa-peri-hexabenzocoronene (SHBC), for ultrahigh-rate MSCs (SG-MSCs) with landmark volumetric capacitance. The SG film was prepared by thermal annealing of the spray-coated SHBC-based film, with assistance of a thin Au protecting layer, at 800 °C for 30 min. SHBC with 12 phenylthio groups decorated at the periphery is critical as a precursor for the formation of the continuous and ultrathin SG film, with a uniform thickness of 10.0 nm. Notably, the as-produced all-solid-state planar SG-MSCs exhibited a highly stable pseudocapacitive behavior with a volumetric capacitance of 582 F cm-3 at 10 mV s-1, excellent rate capability with a remarkable capacitance of 8.1 F cm-3 even at an ultrahigh rate of 2000 V s-1, ultrafast frequency response with a short time constant of 0.26 ms, and ultrahigh power density of 1191 W cm-3. It is noteworthy that these values obtained are among the best values for carbon-based MSCs reported to date.
CRIS-Team Scopus Importer:2023-03-20